Detection of metabolic change in glioblastoma cells after radiotherapy using hyperpolarized 13C‐MRI. (3rd May 2021) - Kawai, Tatsuya; Brender, Jeffrey R.; Lee, Jennifer A.; Kramp, Tamalee; Kishimoto, Shun; Krishna, Murali C.; Tofilon, Philip; Camphausen, Kevin A.
Abstract : Dynamic nuclear polarization (DNP) of 13 C‐labeled substrates enables the use of magnetic resonance imaging (MRI) to monitor specific enzymatic reactions in tumors and offers an opportunity to investigate these differences. In this study, DNP‐MRI chemical shift imaging with hyperpolarized [1‐ 13 C] pyruvate was conducted to evaluate the metabolic change in glycolytic profiles after radiation of two glioma stem‐like cell‐derived gliomas (GBMJ1 and NSC11) and an adherent human glioblastoma cell line (U251) in an orthotopic xenograft mouse model. The DNP‐MRI showed an increase in Lac/Pyr at 6 and 16 h after irradiation (18% ± 4% and 14% ± 3%, respectively; mean ± SEM) compared with unirradiated controls in GBMJ1 tumors, whereas no significant change was observed in U251 and NSC11 tumors. Metabolomic analysis likewise showed a significant increase in lactate in GBMJ1 tumors at 16 h. An immunoblot assay showed upregulation of lactate dehydrogenase‐A expression in GBMJ1 following radiation exposure, consistent with DNP‐MRI and metabolomic analysis. In conclusion, our preclinical study demonstrates that the DNP‐MRI technique has the potential to be a powerful diagnostic method with which to evaluate GBM tumor metabolism before and after radiation in the clinical setting. Abstract : Orthotopic brain tumor mice were subjected to 13 C‐MRI using hyperpolarized [1‐13C] pyruvate to investigate the effect of radiation exposure on glucose metabolism by measuring lactate‐to‐pyruvate ratio in the tumor. Tissue sampling was conducted independently to quantify the lactate concentration and LDHA expression by metabolomic and immunoblot analyses, respectively. These indicated an acceleration of lactate‐to‐pyruvate conversion in one of the stem‐like cell‐derived gliomas after an irradiation during a 24‐h period of time.